Small Cell Carcinoma of the Prostate：A Case Report of Long Term Survival - Ryoji TOKIYA; Yoshinari IMAJO; Junichi HIRATSUKA; Shigeki IMAI; Makito KOBATAKE; Eisaku YODEN; Yoshimasa JO; Tohru ARAKI (KAWASAKI MEDICAL JOURNAL (Japanese), 2006)
A 62-year-old man, who was initially thought to be suffering from prostate adenocarcinoma with normal prostate-specific antigen, underwent hormonal therapy and external beam radiotherapy in September 1997. Although the treatment was successful and the patient went into a complete remission, computed tomography performed six months after the initial workup revealed multiple metastases (paraaortic lymph nodes (LNs), liver, and mediastinal LN). Because of the unexpected clinical course, a diagnostic reevaluation was performed and a diagnosis of small cell carcinoma of the prostate was made. Two courses of intraarterial chemotherapy combined with radiotherapy achieved a second complete remission. The patient maintained a relatively good clinical condition with oral etoposides until March 2000, when multiple right lung and neck LN metastases followed by multiple liver, bone, and intracranial metastases were detected. Three courses of systemic chemotherapy combined with focal radiotherapy decreased the symptoms. In April 2001, massive macrohematuria, which was certified as radiation cystitis by cystoscopy, occurred. Despite control of the hemorrhage with embolization via the bilateral internal iliac arteries, his general condition did not recover and he died in July 2001.